Blockchain-Enhanced Multi-Factor Authentication for Securing IIoT - Allyson Eddy; Bram Zoe anak Guillan; Einstein Kent Elias; Eldren Aniell; Shircrayson bin Simon; Muhammad Faisal (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2024)
This paper proposes Blockchain-Enhanced Multi-Factor Authentication (BEMFA) to address the limitations of existing authentication mechanisms in the Industrial Internet of Things (IIoT). BEMFA combines multi-factor authentication (MFA) with blockchain technology to ensure robust, scalable, and tamper-resistant security tailored to IIoT environments. This method dynamically manages roles and permissions, detects malicious devices, and ensures data integrity and authenticity. Our results demonstrate that BEMFA significantly enhances security, addressing critical access control challenges and mitigating risks posed by malicious devices while maintaining data integrity.